Histological Studies on the Retina of the Falcon "S Eye Ball (Circus Cyaneus C.) Under Light and Electron Microscopy: Samawal Jassim Mohamed Al-Robaae1, Shakir Mahmood Mirhish1 and Jehan Mahmood Rajab2 - Al-Robaae, Samawal Jassim Mohamed (The Iraqi Journal of Veterinary Medicine, 2012)
The histological study showed that the retina of falcon"s eyeball was thin at the peripheryand ranges between 0.6-0.8 μ but it was thick at center 1.68-2.64 μ. The retina consists fromten layers: pigmented epithelium, rods and cons layer, external nuclear layer, externalplexiform layer, internal nuclear layer, internal plexiform layer, Gangilionic cells layer,neurofibres layer and internal limiting membrane layer. The ultra-structural study stated thatthe rods and cons layers contained single rods with single and double cons. The retinacharacterized by lacking of the oil droplets in the internal segments of rods with narrowexternal plexiform layer in order to form network connecting rods and cones, horizontal cells,bipolar cells and Muller’s cells.